The Effects that Social Interactions with Bilingual Relatives Generate on Second Cycle Students in the Acquisition of a Second Language at Mont Berkeley School during the 2023 School Year - Marín Barrantes, Sofía (S. Marín B., 2024)
This study explored the effects of social interactions with bilingual relatives on second language acquisition (SLA) among second-cycle students (n=15) at Mont Berkeley School, Montes de Oca, Costa Rica, during the 2023 school year. A qualitative approach was employed, utilizing surveys for students and parents, and student interviews. Findings revealed a discrepancy between self-reported confidence and observed skills, highlighting the need for multi-perspective assessments. Students identified shyness, limited vocabulary, and infrequent practice as challenges. Interactive classroom activities like online presentations were perceived as beneficial by students, and parental use of these resources suggests trust in the school's curriculum. Social interactions with bilingual relatives varied in frequency and purpose, ranging from leisure activities (music, games, TV) to career aspirations. These interactions contributed positively to SLA through exposure to diverse vocabulary, cultural nuances, and intrinsic motivation. School-provided didactic materials influenced family support, suggesting potential for L2 learning resources that encourage interactive participation at home. The findings contribute to understanding the role of social interactions and highlight the importance of collaborative efforts between school and families in promoting L2 acquisition.